2015
DOI: 10.1159/000377683
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lysate Increases the Percentage of Natural Killer T Cells in Peripheral Blood and Alleviates Asthma in Children

Abstract: Aims: To assess the efficacy of conventional treatment combined with bacterial lysate [OM-85 Broncho-Vaxom (BV)] in the prevention of asthma in children as well as its influence on the number of natural killer T (NKT) cells and their cytokine production. Materials and Methods: Sixty children diagnosed with asthma were divided into either a BV-treated group (with oral OM-85 BV) or a conventional inhaled corticosteroid (ICS) group. The numbers of NKT cells and CD4+ NKT cells were measured in the peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 18 publications
(18 reference statements)
1
45
0
4
Order By: Relevance
“…74,75 Mechanistic studies have confirmed pleiotropic immunomodulating effects on both innate and adaptive immunity. 76,77 Pidotimod, a synthetic dipeptide molecule, induces a variety of immunomodulatory effects 78,79 and has shown some efficacy in preventing RTIs, although this was not always confirmed. 80,81 Probiotic supplementation has been shown to reduce the incidence, duration, and severity of upper respiratory tract infections through immune modulation 82 and in particular rhinovirus infection through altering nasal innate inflammatory responses.…”
Section: Immunostimulatorsmentioning
confidence: 99%
“…74,75 Mechanistic studies have confirmed pleiotropic immunomodulating effects on both innate and adaptive immunity. 76,77 Pidotimod, a synthetic dipeptide molecule, induces a variety of immunomodulatory effects 78,79 and has shown some efficacy in preventing RTIs, although this was not always confirmed. 80,81 Probiotic supplementation has been shown to reduce the incidence, duration, and severity of upper respiratory tract infections through immune modulation 82 and in particular rhinovirus infection through altering nasal innate inflammatory responses.…”
Section: Immunostimulatorsmentioning
confidence: 99%
“…The best understood BL, OM-85 BV (also known as Bronchovaxom) consists of extracts of a mixture of bacterial pathogens causing respiratory tract infections [112]. Human clinical studies have revealed beneficial effects of OM-85 BV on the recurrence of ARTIs and a reduction of associated symptoms [113,114,115,116]. Moreover, other BLs have been shown to reduce the recurrence and duration of ARTIs [117,118] as well as a reduction of atopic dermatitis in infants at heredity risk for atopy [119] (table 1).…”
Section: Interventional Trials Confirm Beneficial Effects Of Probiotimentioning
confidence: 99%
“…В свою очередь, полученные данные явились основанием для изучения возможности профилактического применения препарата ОМ-85 у детей и взрослых с аллергическим ринитом, бронхиальной астмой и хронической обструктивной болезнью легких (ХОБЛ) [47]. Теоретическим обоснованием назначения препарата ОМ-85 пациентам данной категории являются результаты экспериментальных работ, свидетельствующих, что указанный бактериальный лизат обладает позитивным действием на некоторые ключевые звенья патогенеза аллергических заболеваний [36,40,[48][49][50][51][52][53][54][55]. Так, установлено, что под действием препарата ОМ-85 снижается продукция IgE, увеличивается количество T-regсвязанных CD103+ в брыжеечных лимфатических узлах и ускорение их продвижения из кишечника в бронхолегочную систему.…”
unclassified
“…Индуцируется синтез цитокинов Th1-профиля, что приводит к нормализации соотношения IL-4/ИФН-гамма. В результате указанных выше эффектов тормозятся процессы инфильтрации слизистой эозинофилами, нейтрофилами, моноцитами и лимфоцитами, что в целом способствует снижению активности воспаления [36,40,[48][49][50][51][52][53][54][55]. В настоящее время использование бактериальных иммуномодуляторов при аллергических заболеваниях активно изучается и потенциально может открыть новые перспективы в достижении контроля определенных форм бронхиальной астмы, аллергического ринита и ХОБЛ [56][57][58].…”
unclassified